Art disarming philosophy non-philosophy and aesthetics - Shakespeare, Steven, 1968-; Malone, Niamh, 1979-; Anderson, Gary, 1972- (Performance philosophy, 2021)
"This collection brings together an internationally known and interdisciplinary group of scholars, including a major new essay by Laruelle himself. Together they use non-philosophy to cross the boundaries between philosophy and performance"--